2020
DOI: 10.1111/jcmm.15958
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of exosomal miR‐24‐3p in diabetes restores angiogenesis and facilitates wound repair via targeting PIK3R3

Abstract: The incidence of diabetic foot ulcer (DFU) is continuously increasing in elderly diabetic patients. The treatment of DFU in elderly people is often unsatisfactory due to their relatively weak immunity and the vascular lesions caused by diabetes. 1,2 Furthermore, commonly associated diseases with DFU such as infection, gangrene and other serious complications potentially lead to unavoidable amputations and other destructive consequences both the patient's physical and mental health, thereby posing serious threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…Since most of the findings were obtained using exogenously expressed miRNAs, further studies are required to evaluate the translational potential of our results. Nonetheless, our findings are consistent with the observation of miR-24 expression in endothelial cells [ 42 , 43 , 44 , 87 ] and its roles as a regulator of various cerebrovascular phenomena, including angiogenesis in gliomas [ 88 , 89 ] and vasospasm following subarachnoid hemorrhage [ 90 ]. The study also has some strengths, including the fact that the 3′-UTR of Neuropilin-1 that is targeted by miR-24 is highly conserved among species, from primates to rodents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since most of the findings were obtained using exogenously expressed miRNAs, further studies are required to evaluate the translational potential of our results. Nonetheless, our findings are consistent with the observation of miR-24 expression in endothelial cells [ 42 , 43 , 44 , 87 ] and its roles as a regulator of various cerebrovascular phenomena, including angiogenesis in gliomas [ 88 , 89 ] and vasospasm following subarachnoid hemorrhage [ 90 ]. The study also has some strengths, including the fact that the 3′-UTR of Neuropilin-1 that is targeted by miR-24 is highly conserved among species, from primates to rodents.…”
Section: Discussionsupporting
confidence: 91%
“…Our data on miR-24 are in agreement with previous studies exploring the functional role of miR-24 in endothelial cells. Indeed, miR-24-3p has been shown to regulate angiogenesis in rodents, zebrafish embryos, and in diabetic patients by modulating endothelial function [ 42 , 43 ]. Additionally, miR-24 has been demonstrated to reduce endothelium-dependent inflammatory responses [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the ndings were obtained using exogenously expressed miRNAs, further studies are required to evaluate the translational potential of our results. Nonetheless, our ndings are consistent with the observation of miR-24 expression in endothelial cells [42][43][44]87] and its roles as a regulator of various cerebrovascular phenomena, including angiogenesis in gliomas [88,89] and vasospasm following subarachnoid hemorrhage [90]. The study also has some strengths, including the fact that the 3′-UTR of Neuropilin-1 that is targeted by miR-24 is highly conserved among species, from primates to rodents.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, miR-24-3p has been shown to regulate angiogenesis in rodents, zebra sh embryos, and in diabetic patients by modulating endothelial function [42,43]. Additionally, miR-24 has been demonstrated to reduce endothelium-dependent in ammatory responses [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the validation cohort, the expression of hsa-miR-3184-3p , hsa-miR-24-3p , and hsa-miR-197-3p were confirmed to be upregulated in PDR patients, and anti-VEGF therapy significantly downregulated their expression. Based on previous literature, miR-24-3p has also been demonstrated to be rich in diabetic exosome, which induces a highly limited mRNA expression of phosphatidylinositol 3-kinase regulatory subunit gamma (PIK3R3), and the reduction of PIK3R3 inhibited human umbilical vein endothelial cell (HUVEC) proliferation, migration, and angiogenesis, as well as inducing HUVEC apoptosis ( Xu et al, 2020 ). Another research has a similar finding—extremely high miR-24-3p level in exosomes was derived from microglial cells that were injected into the vitreous of oxygen-induced retinopathy (OIR) mice, and it showed that exosome-treated OIR mice exhibited smaller avascular areas and fewer neovascular tufts in addition to decreased VEGF and transforming growth factor β (TGF-β) expression ( Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%